(untitled) (Global Journal of Human-Social Science, 2019)
Jubail University College follows a strict language deduction policy for written exams in all courses in the English Language Program for bachelor students 20 of the total number of marks is deducted for each written formal exam This research explores student s attitude towards this policy as well as its effectiveness in improving student s performance It outlines problems encountered by the students as well as recommendations to further improve student performance A total of 32 female students from various levels at Jubail University College participated in this study A survey was distributed to investigate the problem The results of the research showed that the language deduction policy is effective to some extent in terms of making students more aware of their need to improve their language proficiency however it failed to provide practical solutions for students development